The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2265.2007.03070.x
|View full text |Cite
|
Sign up to set email alerts
|

Three years prospective investigation of anterior pituitary function after traumatic brain injury: a pilot study

Abstract: GH deficiency is the most common pituitary deficit 1 and 3 years after TBI. In patients with mild and moderate TBI, pituitary function improves over time in a considerable number of patients, but it may also worsen rarely over the 3-year period. In patients with severe TBI, ACTH and GH deficiencies at 1st year evaluation persist at 3rd year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 25 publications
4
86
2
7
Order By: Relevance
“…This prevalence of hypopituitarism is much lower compared with the prevalence rates reported in the majority of the previous studies (15-90%) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This might be explained by the use of different endocrine tests and cutoff values (19).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This prevalence of hypopituitarism is much lower compared with the prevalence rates reported in the majority of the previous studies (15-90%) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This might be explained by the use of different endocrine tests and cutoff values (19).…”
Section: Discussioncontrasting
confidence: 49%
“…The available cohort studies investigating the prevalence of pituitary insufficiency report a percentage ranging from 15 to 90% (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). There are several explanations for this remarkably wide range in reported prevalence, including differences in inclusion criteria and duration of follow-up since TBI (short-versus longterm follow-up), and the use of different tests, and cutoff values (19).…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies used basal free thyroxine (FT 4 ) and TSH levels only. Within these studies, the cut-off value for decreased FT 4 varied between 8 and 12 pmol/l (2,5,7,11,14,18,19). In two studies, reference values were not reported (4, 10), one of which (Bushnik et al) reported the highest prevalence of secondary hypothyroidism.…”
Section: The Hypothalamus-pituitary-thyroid Axismentioning
confidence: 99%
“…In recent years, an increasing number of studies have reported the presence of pituitary insufficiency in patients who experienced traumatic brain injury (TBI) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The prevalence of pituitary insufficiency after TBI appeared to be unexpectedly high (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation